Pembuatan Roullade Ikan Patin (Pangasianodon Hypophthalmus) Tempe Gembus dengan Layer Daun Semanggi (Marsilea Drummondii) Ditinjau Sifat Organoleptik - Mutiara Kinanti Ananda; Any Sutiadiningsih; Ila Huda P. D; Lucia Tri Pangesthi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
Innovation in fish processing, such as Roullade Fish, offers an effective way to increase consumption. Roullade is a dish made by rolling or wrapping minced meat with a filling. Roullade Fish utilizes patin fish due to its thick flesh, minimal bones, and rich nutritional content, including essential amino acids and omega-3 fatty acids. The addition of tempe gembus enhances the texture and nutritional value of the roullade by providing fiber and glutamic acid. Tempe gembus also imparts a distinctive umami flavor. To enrich the nutrition and appearance, the roullade is coated with a pure of daun semanggi, adding natural aroma and color. This combination is expected to yield a high-quality product with a taste preferred by consumers.This study aims to determine the characteristics of making a roulade using striped catfish, tempe gembus, and layered clover leaves in terms of organoleptic properties, nutritional content, and panelist preference. The research method used is experimental, as it aims to identify the effects of using striped catfish, tempe gembus, and clover leaves on the influenced variables.Based on the research results on the preparation of Roullade with patin fish, tempe gembus, and daun semanggi layer, the formulation with 70% patin fish, 30% tempe gembus, and 10% daun semanggi achieved the highest scores in color, shape, texture, aroma, and taste. Its nutritional content includes 16.86% protein, 5.10% fat, 38.90% carbohydrates, 3.60% fiber, and 30.60% water. This formulation provides optimal organoleptic quality and balanced nutritional content.